2014
DOI: 10.1007/s10461-014-0888-7
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Their Status to Youth with Human Immunodeficiency Virus Infection in the Dominican Republic: A Mixed-Methods Study

Abstract: A mixed-methods study was conducted to determine the proportion of HIV-infected children who knew their status, identify characteristics associated with children’s knowledge of their status, and describe caregivers’ and adolescents’ experiences relevant to disclosure in the Dominican Republic (DR). Of 327 patients aged 6–18 years treated in the principal DR pediatric HIV facilities, 74 (22.6%) knew their status. Patients aged 13 years or older and/or who had participated in non-clinical activities for HIV-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…A possible reason for this low rate of the disclosure may be because most of the children that took part in this study were younger as observed with a mean age of ten years. Though this rate of disclosure is low, it is higher than those reported in Kenya, the Dominican Republic, Zimbabwe, and Ghana, 23,47,48,49 which ranged between 21% and 33%.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…A possible reason for this low rate of the disclosure may be because most of the children that took part in this study were younger as observed with a mean age of ten years. Though this rate of disclosure is low, it is higher than those reported in Kenya, the Dominican Republic, Zimbabwe, and Ghana, 23,47,48,49 which ranged between 21% and 33%.…”
Section: Discussioncontrasting
confidence: 54%
“…Hence caregivers felt the need to refrain from disclosing until their child was old enough to understand such information before they could be told their status. Previous studies have reported that caregivers preferred to disclose to older adolescents than younger children 23,49,50 . Beck‐Sagué and colleagues 49 found among Dominicans that caregivers of younger children did not disclose their status because they felt their child had not reached the stage where they could understand and cope effectively with their condition.…”
Section: Discussionmentioning
confidence: 99%
“…Findings showed that the rate of full disclosure of status to children living with HIV is still low in Ghana. Although this rate of disclosure is considered to be low, it is slightly higher compared to those reported in Kenya [ 31 ], the Dominican Republic [ 29 ], Zimbabwe [ 32 ], and earlier figures reported in Ghana [ 15 ]. The low rate of disclosure of HIV status could be attributed to the fact that the majority of the children who participated in this study were younger, and it has been established that older children and adolescents are more likely to have their HIV status disclosed to them than younger children [ 15 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 55%
“…Although more than half of disclosures were led by children’s family members, accidental disclosures by friends and other persons were also reported, which requires further attention. As a previous study pointed out [ 26 ], accidental disclosure might be a more stressful event for children than that by their caregivers and/or health care workers, and it would have negative impact on them contrary to the prepared disclosure process.…”
Section: Discussionmentioning
confidence: 99%